2021
DOI: 10.1021/acsanm.1c01339
|View full text |Cite
|
Sign up to set email alerts
|

Few-Layer PdSe2 Nanofilm/Si Heterojunction for Sensing NO2 at Room Temperature

Abstract: Palladium diselenide (PdSe 2 ), a noble transition metal dichalcogenide has attracted increasing attention in recent years due to its outstanding semiconductor properties. In this study, 2D PdSe 2 nanofilms with thicknesses ranging from 2 to 28 nm and their heterostructures with Si substrates (PdSe 2 /Si heterostructures) were synthesized via a simple selenization method. Electrical transport characterizations based on field-effect transistor devices indicate that the few-layer PdSe 2 nanofilms exhibit a p-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 69 publications
0
33
0
Order By: Relevance
“…1(c), the major peaks at 337.1, 342.3, 55.0, and 55.9 eV observed in the PdSe 2 spectrum are assigned to Pd 3d 5/2 , Pd 3d 3/2 , Se 3d 5/2 , and Se 3d 3/2 , respectively. 11 Besides, the peak positions with the binding energies of 444.6, 452.2, 54.2, and 55.0 eV in the InSe XPS can be attributed to In 3d 5/2 , In 3d 3/2 , Se 3d 5/2 , and Se 3d 3/2 , respectively. 24 The full spectra and the elemental compositions of the PdSe 2 and InSe films after fitting with the mixed Gaussian–Lorentzian function are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…1(c), the major peaks at 337.1, 342.3, 55.0, and 55.9 eV observed in the PdSe 2 spectrum are assigned to Pd 3d 5/2 , Pd 3d 3/2 , Se 3d 5/2 , and Se 3d 3/2 , respectively. 11 Besides, the peak positions with the binding energies of 444.6, 452.2, 54.2, and 55.0 eV in the InSe XPS can be attributed to In 3d 5/2 , In 3d 3/2 , Se 3d 5/2 , and Se 3d 3/2 , respectively. 24 The full spectra and the elemental compositions of the PdSe 2 and InSe films after fitting with the mixed Gaussian–Lorentzian function are shown in Fig.…”
Section: Resultsmentioning
confidence: 87%
“…10 Recently, PdSe 2 and InSe have been reported as the promising room-temperature gas sensing materials due to their unique crystal structures and properties. 11,12 Furthermore, the vdWs heterostructures formed by two different TMDs materials can compete with or even be superior to conventional bulk semiconductor junctions and respective 2D constituent because of their atomically sharp interfaces and designed energy band alignments. 13 Recent studies have shown that the vdWs heterostructures devices with outstanding performance have been widely investigated in the fields of photodetectors, field-effect transistors (FETs), solar cells, and room-temperature gas sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for preparing other low-dimensional Reproduced with permission. [220] Copyright 2021, American Chemical Society. c) SEM image of a pentagonal PdSe 2 nanosheet (cathode) protruding from metal lead 1 and the anode W-tip used for field emission measurements.…”
Section: On-demand Synthesismentioning
confidence: 99%
“…Afterwards, the gas sensor of PdSe 2 /Si heterostructure is experimentally demonstrated and they analyzed the charge transfers between the PdSe 2 surface and molecules of C 2 H 5 OH, CO, H 2 , NH 3 , NO, and NO 2 , respectively ( Figure a). [ 220 ] The gas sensor presents excellent selectivity and the highest response of 42% toward 5 ppm NO 2 among the six studied gases at room temperature (Figure 14b), due to the specific surface morphology and p‐n heterostructure effect. Meanwhile, the gas sensor with an excellent response of about 7.2% toward 100 ppb NO 2 gas shows extremely low limit of detection, indicating the promising applications of pentagonal 2D materials for consumer electronics, industrial safety, medical and health, environmental protection, and aerospace after their response and recovery times can be further improved.…”
Section: Gas Sensing and Field Emission Applicationsmentioning
confidence: 99%
See 1 more Smart Citation